THE DEVELOPMENT OF THE ECONOMY AND MONEY CIRCULATION IN THE EMIRATE OF BUKHARA DURING THE PERIOD OF THE MANGYTS - Zamonov Akbar Turg‘unovich; Hakimova Xandona Oybek qizi (American Journals Publishing, 2023)
This article discusses the basics and functions of the activities of the Bukhara branch of Russian commercial banks in the emirate of Bukhara. In Soviet historiography, banks were understood as a means of Western and Russian "colonialism". The author, based on archival data, proves that the financial institutions of the Russian empire, unlike Soviet and post-Soviet researchers, believe that banks were not "monopolists" in the economy of Central Asia. The largest bank in the region (12 branches) with an extensive network of branches throughout Central Asia is the Russo-Asian commercial bank (Russian Chinese bank until 1910). It should be noted that the Russian-Asian bank sought to take control of cotton and industrial production. But in the end it could not become a locomotive of the economic development of the region. The author believes that the main reason is to adapt to the existing economic relations in the governorates and khanates of Turkestan. In understanding banks, the "modernization" of the economy of Central Asia consisted of financing export crops and mediation between the metropolis and the periphery. The periphery of the "colony" at first glance seemed to be an attractive area for investment and excessive profit, but the speculative nature of the Turkestan economy prevented the normal development of banks. As a result, the economic "modernization" of Central Asia slowed down and paved the way for the Soviet experience.
Keywords: banks, commerce, branch, monopoly, financing, economic modernization